Hydrogen Peroxide Is Involved in β-Cyclodextrin-hemin Complex-Induced Lateral Root Formation in Tomato Seedlings - Cui, Weiti; Zhu, Dan; Shen, Wenbiao; Mei, Yudong; Hu, Dekun; Shi, Yujian; Ren, Yong; Shen, Wei; Gu, Quan; Xu, Daokun; Huang, Liqin (Frontiers in Plant Science, 2017)
Although previous results showed that β-cyclodextrin-hemin complex (β-CDH) could induce tomato lateral root (LR) formation, the corresponding downstream messengers are still not fully understood. In this report, similar to the inducing effects of exogenously applied hydrogen peroxide (H2O2), we discovered that β-CDH elicited RBOH1 transcript upregulation, endogenous H2O2 accumulation, and thereafter tomato LR development. Above responses were sensitive to dimethylthiourea (DMTU) and ascorbic acid (AsA), two membrane-permeable scavengers of H2O2, showing that accumulation of H2O2 and LR formation were significantly blocked. The test with diphenylene idonium (DPI; the inhibitor of NADPH oxidase) revealed that H2O2 mainly produced by NADPH oxidase, might be involved in LR formation triggered by β-CDH. qPCR combined with pharmacological and anatomical analyses showed that β-CDH-modulated several marker genes responsible for LR formation, such as CYCA3;1, CYCA2;1, CYCD3;1, and CDKA1 (four cell cycle regulatory genes), ARF7 and RSI-1 (two auxin signaling genes), LAX3 (an auxin influx carrier), IAA14 (encoding a member of the Aux/IAA protein family), PIN3 and PIN7 (two auxin efflux carriers), isocitrate dehydrogenase [NADP], NADH-cytochrome b5 reductase 1, and L-ascorbate oxidase homolog genes (two reactive oxygen species-associated genes and one LR formation-related gene), were causally related to above H2O2 signaling. Particularly, representative proteins related to H2O2 metabolism and lateral rooting, were specifically induced in β-CDH-treated tomato seedlings. Overall, the results clearly suggested a vital role of H2O2 in the β-CDH-induced tomato lateral root formation, and β-CDH-elicited H2O2-related target proteins responsible for LR formation might be, at least partially, regulated at transcriptional and translational levels.